Perbandingan Frekuensi Resistensi Bakteri Bacillus subtilis terhadap Antibiotik Tetracycline Tunggal dan Kombinasi dengan Dekokta Hibiscus sabdariffa L. - Nova Faisal Waber; Rio Risandiansyah; Hardadi Airlangga (Published by Faculty of Medicine Universitas Islam Malang, 2017)
Introduction: The use of inappropriate antibiotics encourages the emergence of antibiotic resistance. It can be known by measuring the frequency of resistance. The use antibiotic combination has a low resistance, but the combination of antibiotic with herb is unknown.This study was conducted to prove the comparison frequency of bacterial resistance of Bacillus subtilis to Tetracycline and combination with dekokta Rosella (Hibiscus sabdariffa L.).Methods: This research uses laboratory experimental method in vitro. The method used is to measure the zone of inhibition which is then used to determine the minimum inhibitory (KHM). Then, the measurement of resistance frequency on the media with 3 times repetition.Results: Zone Inhibition of dekokta Rosella with the highest concentration (100%) is 15 mm, while the Tetracycline antibiotic is 40 mm. KHM Tetracycline antibiotic is 1/1024 which is equivalent to 0.0048 mg / ml and dekokta Rosella is 1/16 equivalent to 6.25 mg / ml. The frequency of resistance in Tetracycline is 0.69 x 10-9 to 9.72 x 10-9. Meanwhile, in Rosella dekokta not found any resistant bacteria. In combination between dekokta Rosella and Tetracycline antibiotics, there was no antibiotic resistant to B. Subtilis bacteria.Conclusion: From this research can be concluded that dekokta Rosella (Hibiscus sabdariffa L.) can be used as a combination with antibiotics to reduce resistance frequency of Bacillus subtilis to TetracyclineKeywords: Resistance, Resistance Frequency, Tetracycline, Rosella (Hibiscus sabdariffa L.)